Optimalisasi Fungsi Masjid Sebagai Pusat Ekonomi Masyarakat Berbasis Masjid Di Kota Medan Dalam Perspektif Ekonomi Islam - Rambe, Trinaningsih; Rokan, Mustapa Khamal; Harahap, Muhammad Ikhsan (Jurnal Manajemen Akuntansi (JUMSI), 2024)
This study aims to determine the potential of land,knowing the potential of the congregation, the potential of Infaq, mosques in the city of Medan. The method used in this study is a qualitative method with a descriptive approach that is by observation, interview and documentation with 4 BKM Masjid Al-Jihad, Masjid Raya Al-Mashun, Masjid Al-Musannif, and Masjid complex Al-Musabbihin Medan. The results of this study indicate that the optimization of the function of the mosque as the economic center of the mosque-based community in the city of Medan with aspects of land potential is the mosque as a place of worship and supporting facilities. Optimization of land potential for economic activities can be done by carrying out business activities by reviving mosque cooperatives and green economy by utilizing vacant land. On the potential aspects of worshipers so far only for worship activities,. Optimizing the potential of pilgrims for economic activities can be done by empowering women and housewives to produce products that can be sold, making management for pilgrims who are responsible in the field of Economics. The potential aspect of Infaq funds is quite large. The potential of Infaq funds is only used for mosque operations, mosque construction and for educational activities. Optimizing the potential of Infaq funds can be done by distributing productive zakat in the form of providing business capital for pilgrims who are less able to have the intention and willingness to entrepreneurship.